The response of the ionosphere to intense geomagnetic storms in 2012 using GPS-TEC data from East Africa longitudinal sector. (December 2015) - Tesema, F.; Damtie, B.; Nigussie, M.
Abstract: The response of the ionosphere to intense magnetic storms has been studied using total electron content (TEC). TEC data recorded by a series of GPS receivers at a longitude ∼ 35 ° E covering a wide range of latitudes ( 32 ° S to 68 ° N, geographic) is analyzed to study spatio-temporal modifications of the vertical TEC (vTEC) during storms on 07 and 09 March 2012 and on 14 July 2012. We have observed main phase positive response at equatorial ionization anomaly (EIA) crests and mid latitude regions in all the storms. These main phase positive responses are associated with vertical drift enhancement (intensified equatorial electrojet (EEJ)) and the mechanical effect of equatorward neutral wind after an auroral activity. A daytime substantial depletion of TEC at low latitude region was observed on 08 March 2012. This is due to the combined effects of oversheilding and disturbance dynamo electric field that drive large downward drifts during the day. The low latitude and equatorial ionospheric response in the recovery phase days of March storm is found to be largely associated with the disturbance dynamo field that suppressed the upward E × B drift from EEJ observations. The summer negative and winter positive response in July storm as well as mid latitude positive response in March storm was associated with the composition changes as depicted by the O to N 2 ratio from GUVI measurements. Abstract : Highlights: We have observed significant variations of TEC during disturbed times. Main phase daytime EIA enhancement is associated with penetration electric field. Seasonal effect in the ionospheric response was clearly seen on July storm. Low latitude disturbance dynamo electric field dominated in March storm.